Prediction ability of a new minimum bubbling criterion - Cherntongchai P. (2014)
The recently developed minimum bubbling criterion of Brandani and Zhang [19] for a prediction of the minimum bubbling point was validated using an experimental determination of the minimum bubbling points of spherical rigid non-porous powders with various particle size distributions. These powders include a narrow size cut powder, a "natural" size distribution powder and a "bimodal" size distribution powder. The minimum bubbling points were correctly identified using the εd and Ud characteristic curves, obtained from a correct interpretation of 1-valve and 2-valve bed collapse curves using the bed collapse model, developed by Cherntongchai and Brandani in [21]. In order to enhance the prediction ability of the stability criterion, an appropriate drag force correlation was introduced into the criterion. Then, it was pointed out that the characteristic parameter of the criterion has a strong dependence on the voidage term as an exponential function. As a result, a simple empirical correlation is proposed. The new stability criterion was, then, tested against a detailed comparison of 700 minimum bubbling points taken from literature. The criterion can very well predict the minimum bubbling voidage for various operating conditions of rigid non-porous materials and predict fairly well the minimum bubbling velocity. © 2012 The Society of Powder Technology Japan. Published by Elsevier B.V. and The Society of Powder.